PENGARUH KEMAJUAN TEKNOLOGI INFORMASI DAN PENGETAHUAN INVESTASI TERHADAP MINAT INVESTASI GENERASI MILENIAL DI PASAR MODAL - Andi Kusuma Negara; Hendra Galuh Febrianto (Business Management Journal, 2020)
The number of millennial or forces born between 1981-2000 according to the 2017 National Socioeconomic Survey (Susenas) counts 88 million people or 33.75 per cent of Indonesia's population (BPS). PT Indonesian Central Securities Depository (KSEI) noted that young people or millennial generation still count the number of investors in the Indonesian capital market. Throughout 2018 the number of young investors reaching 21-30 years won 39.72% of the number of investors. Therefore BEI participated in using the Indonesian Central Securities Depository (KSEI) & securities companies began to hold a variety of lessons ranging from talk shows, seminars to workshops & capital market schools (SPM) information technology and investment knowledge. This research method is a causal relationship research with quantitative data with SPSS tools. contributing to this research were students of the faculty of economics and business at the University of Muhammadiyah Tangerang with a sample of 92 respondents. the results of this study indicate the fact that the development of information technology is significant to the investment interests of millennial. While investment knowledge has a positive and significant impact on investment interests in millennial.